Home networking : the missing manual - Lowe, Scott (Missing manual., 2005)
Millions of computers around the world today are connected by the Internet, so why is it still so hard to hook up a few PCs in you own home? Whether you want to share an Internet connection, install WiFi, or maybe just cut down on the number of printers you own, home networks are supposed to help make your life easier. Instead, most aspiring home networkers get lost in a confusing maze of terms and technologies: 802.11g, Fast Ethernet, Cat 5 cable (or was it Cat 5e?), Powerline, and on and confusingly on.That's where Home Networking: The Missing Manual comes in. Using clear language, straightforward explanations, and a dash of humor, this book shows you how to do everything you need to set up a home network. Coverage includes:WiFi, Ethernet, or Powerline? There are several kinds of digital pipes that you can use to create your network, and none of them have friendly names. This book tells you what they are, explains the pros and cons of each, and helps you figure out what you need to buy, and how to install it.Windows and Mac info included. Half the battle in home networking takes place after you've bought your gear and plugged it in. That's because the routers, network adapters, and cables that you need get you only part way towards networking nirvana. Whether you've got PCs or Macs or both, you'll need help tweaking your computers' settings if you want to get all your machines talking to each other. This book covers most known operating system flavors, including Windows XP, 2000, Me, and 98, and Mac OS X and OS 9.Fun things to do with your network. The real fun starts once your network is up and running. This book shows you how to do much more than simply share an Internet connection and a printer. You'll learn how to stream music from your PCs to your stereo, how to display pictures on your TV, how to hook up game consoles to your network, and more!Most important, this book helps you understand the difference between what you need to know to create and use your home network and what's best left to those looking for a career as a system administrator. In Home Networking: The Missing Manual you'll find everything you need to get your network running-and nothing more.